APLIKASI DRONE-UAV UNTUK SURVEY DAN PEMETAAN MENGGUNAKAN COPTER PADA PERKEBUNAN KELAPA SAWIT (Studi Kasus : Bahruny Group, PT. Satya Agung, Lhoksemawe, Aceh) - Dede Ardiansyah (Universitas Negeri Medan, 2021)
Drone is a UAV vehicle which is currently widely used in various activities, one of which is for aerial photography (photogrammetry). The concept of efficiency is the main goal of using this drone, which is to produce detailed and up-to-date aerial photo images with adjustable area coverage, relatively short time, affordable costs and minimal personnel required. The output is an orthophoto image that already has coordinates and can be used as primary data for convenience in the tree counting process so that tree populations in blocks based on design and area statements can be known in detail and accountably. The aerial mapping process using a copter unmanned vehicle with a height of 80-meters above ground level at an image resolution of 2.23 cm/pixel produces 3,795 photos with side overlap and front overlap photos of 70% and 80% with an area covering 2.72 km2 or 272 ha. The results of the calculation of oil palm trees as many as 3,147 pkk with a statement area of 29.08 ha in Block M06 and obtained an SpH of 108 pkk which is smaller than the ideal SpH ranging from 135-143 pkk/ha so that there is a need for compaction activities or plant fulfillment in the block.